Reproduction and pathogenicity of Meloidogyne incognita on chickpea cultivar ‛Nacional-29’ - Mayra Guadalupa Rodríguez Hernández (Centro Agrícola, 2019)
To determine the reproduction and pathogenicity of nematode Meloidogyne incognita (Kofoid and White) Chitwood on chickpea cultivar ‘Nacional-29' were the objectives of this work conducting in semi-controlled conditions. Using 1 kg capacity pots, four treatments were establishing in correspondence with the following initial nematode population levels (Pi) with 0 (control); 1,5; 2,5 and 5 eggs and second stage juveniles per gram of substrate. The experiment was conducted during 35 days and, at the end of this period, the stem/leaves and roots fresh biomass, number of galls in roots, Root galling index, final population and the Reproduction Factor were determined. The data were analyzed through Simple Variance Analysis and the relationship between Pi and the stem/leaves fresh biomass was determined by regression analysis. The chickpea ‘Nacional-29' cultivar was good host and susceptible to M. incognita, with variable values and superior than 1. The root biomass showed statistic differences between treatments and stem/leaves fresh biomass decrees with the increment of initial population levels of M. incognita. The negative impact of increased initial population of M. incognita in "Nacional 29" chickpea cultivar, aspect that the farmers must take in consideration.